2010
DOI: 10.1146/annurev-immunol-030409-101218
|View full text |Cite
|
Sign up to set email alerts
|

From Allergen Genes to Allergy Vaccines

Abstract: IgE-mediated allergy is a hypersensitivity disease affecting more than 25% of the population. The structures of the most common allergens have been revealed through molecular cloning technology in the past two decades. On the basis of this knowledge of the sequences and three-dimensional structures of culprit allergens, investigators can now analyze the immune recognition of allergens and the mechanisms of allergic inflammation in allergic patients. Allergy vaccines have been constructed that are able to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
174
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 231 publications
1
174
0
4
Order By: Relevance
“…Analysis of Der p1 revealed the presence of smaller fragments, sized 25 kDa (a), 17 kDa (b), and 14 kDa (c, Figure 1B). These fragments correspond to Der p1 breakdown products given the endogenous cysteine protease activity of Der p1 11, 12. Maldi‐TOF analysis on these fragments confirmed their identity as Der p1 peptides (Figure 1B).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Analysis of Der p1 revealed the presence of smaller fragments, sized 25 kDa (a), 17 kDa (b), and 14 kDa (c, Figure 1B). These fragments correspond to Der p1 breakdown products given the endogenous cysteine protease activity of Der p1 11, 12. Maldi‐TOF analysis on these fragments confirmed their identity as Der p1 peptides (Figure 1B).…”
Section: Resultsmentioning
confidence: 75%
“…Treatment options for HDM allergy include allergen avoidance and SIT 11. However, HDM extracts are variable in content of allergens,12, 13 and stability is limited 14. Given the fact that sensitization to Der p1 and 2 identifies more than 95% of HDM‐allergic individuals9, 13 and their causal role in early sensitization,10 SIT with purified Der p1 and 2 might be a more attractive therapeutic approach compared to the use of HDM extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of the disease-causing allergens is not only important to study the mechanisms of wheat food allergy, but also to improve diagnosis and therapy (18). The structure of wheat allergens can be either identified by proteomic approaches (19) or by molecular cloning technologies (20).…”
mentioning
confidence: 99%
“…[18,20]. Studies using recombinant allergens and defined allergen epitopes for analysis, as well as SIT trials performed with purified recombinant allergens and recombinant hypoallergenic allergen derivatives, have confirmed that a major mechanism of SIT is the induction of allergen-specific IgG-blocking antibodies [14,25,36,37]. Moreover, it has been demonstrated that allergen-specific blocking IgG can also inhibit IgE-facilitated allergen presentation by antigen-presenting cells to T cells and thus suppress allergen-induced T-cell activation [13,38,39].…”
Section: Milestones In the Development Of Sitmentioning
confidence: 99%
“…Allergen sequences became available, avoiding the need for cumbersome purification of allergen components from natural allergen extracts. A new phase in the development of SIT began with the ability to produce synthetic peptides, pure recombinant allergens and hypoallergenic allergen derivatives for SIT [25]. With the aim of inducing T-cell tolerance, allergen-derived T-cell epitope-containing synthetic peptides were administered to allergic patients in immunotherapy trials approximately 10 years later [26].…”
Section: Milestones In the Development Of Sitmentioning
confidence: 99%